Engaging EFL Teachers in Reflective Practice as A Way to Pursue Sustained Professional Development - Joko Nurkamto; Teguh Sarosa (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2020)
Reflective practice has become a significant aspect in determining good teaching and learning practices and is an important part of professional practice and professional growth. However, English teachers in Indonesia has not been able to perform reflection on their teaching in order to improve their teaching practice. This study reports the results of an intensive training held by PKM UNS to help teachers develop a reflective teaching habit. The participants were 30 English teachers of Islamic Senior High School in Solo Raya. Observation field notes and teacher assignments were used as the main data collection method. From this program, it was found that the English teachers encountered plethora of challenges in developing reflective practice due to their lack of understanding of reflective teaching. However, the teachers show an improvement in implementing reflective teaching strategies after their participation in the training. Recommendations to include reflective practices in teacher professional development programs is drawn based on the findings.